Vortex lattice of a long superconducting wire with a columnar defect - Sardella, Edson [UNESP]; Freire, Rodrigo de Alvarenga [UNESP] (Sociedade Brasileira de Física, 2002)
In the present work we study a long superconducting wire with a columnar defect in the presence of an applied magnetic field. The cross section of the cylinder is assumed to be circular. The field is taken uniform and parallel to the cylinder axis. We use the London theory to investigate the vortex lattice inside the wire. Although this theory is valid in the limit of low vortex density, that is, when the nearest neighbor vortex distance is much larger than the coherence length, we can obtain a reasonable qualitative description of lattice properties. We calculate: (1) the vortex lattice structure using the simulated annealing technique; (2) the magnetization curve as a function of the applied field.